1994
DOI: 10.1063/1.358369
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical predictions of interface anisotropy in the presence of interdiffusion (invited)

Abstract: The first ab initio electronic structure calculations of the magnetocrystalline anisotropy of superlattices with imperfect interfaces are presented. Specifically the possibility of an interdiffusion between the layers at the interface in Co/Pd and Co/Pt superlattices is considered. The electronic structure calculations use the local spin-density formalism as implemented with the layer Korringa–Kohn–Rostoker method. Interdiffusion at the interface is modeled in two distinct ways. In the first approach a diffuse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…3 Attempts are under way to include the effects of interface disorder, surface steps, and other imperfections. 4,5 But questions remain even for ideal systems like bulk Fe and Ni. For Ni in particular it is not clear at all at this point if the LSDA leads to the correct easy axis.…”
Section: Department Of Physics Oregon State University Corvallis Omentioning
confidence: 99%
“…3 Attempts are under way to include the effects of interface disorder, surface steps, and other imperfections. 4,5 But questions remain even for ideal systems like bulk Fe and Ni. For Ni in particular it is not clear at all at this point if the LSDA leads to the correct easy axis.…”
Section: Department Of Physics Oregon State University Corvallis Omentioning
confidence: 99%
“…[1][2][3][4][5] Co-Pd and Co-Pt alloy films were since found to exhibit PMA, and relationships between alloy composition, preparation conditions, microstructure, and magnetic properties have been established. [6][7][8][9][10][11] Weller et al 7,9 reported that Co-Pt and Co-Pd alloys have PMA, 100% remanence, and high coercivity comparable to those in their multilayer systems.…”
mentioning
confidence: 98%
“…A polarized extended x-ray absorption fine structure ͑EXAFS͒ study of Co-Pt alloy films concludes its origin is likely to be clustering ͑ordering͒ of Co atoms in surface normal ͑111͒ planes yielding internal interfaces 12 based on a model of intermixing at the interface of superlattice. 4 As for the Co-Pd alloy, the origin of its PMA was speculated to be a similar compositional anisotropy of Co atoms in the Pd matrix 10 without direct evidence. The origin of PMA in the alloys has remained unclear because of limited direct structural information and lack of theoretical study while the PMA in multilayers has been explained by the interfacial, magnetocrystalline, and magnetoelastic anisotropy ͑MEA͒ originating from the uniaxial asymmetry.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…On the other hand, it acts to reduce magnetocrystalline anisotropy (MCA) [10]. Defects from interdiffusion also reduce magnetic anisotropy [11]. Hence, depending on the strength of each contribution, PMA may be enhanced or reduced by the surface roughness.…”
mentioning
confidence: 99%